A Simple Approach to Distinguish Classic and Formaldehyde-Free Tannin Based Rigid Foams by ATR FT-IR - Gianluca, Tondi; Martin, Link; Chuan, Wei Oo; Alexander, Petutschnigg (Hindawi Publishing Corporation, 2015)
Tannin based rigid foams (TBRFs) have been produced with formaldehyde since 1994. Only recently several methods have been developed in order to produce these foams without using formaldehyde. TBRFs with and without formaldehyde are visually indistinguishable; therefore a method for determining the differences between these foams had to be found. The attenuated total reflectance infrared spectroscopy (ATR FT-IR) investigation of the TBRFs presented in this paper allowed discrimination between the formaldehyde-containing (classic) and formaldehyde-free TBRFs.Thespectra of the formaldehyde-free TBRFs, indeed, present decreased band intensity related to the C–O stretching vibration of (i) the methylol groups and (ii) the furanic rings. This evidence served to prove the chemical difference between the two TBRFs and explained the slightly higher mechanical properties measured for the classic TBRFs.